IJSD Volume 6 2016 Field Perceptions: Full Issue - Bench, Harmony; Ellis, Simon (The International Journal of Screendance, 2016)
The full issue of IJSD vol. 6 (2016). Please note: For the best offline reading experience, please print double-sided on 8.5x11 paper. Links to online sources are live in the PDF if read onscreen.